1998
DOI: 10.1017/s0033291798007648
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of depression among community-dwelling elderly African-American and White older adults

Abstract: This study confirms earlier findings of minimal overall differences in symptom frequency between African-American and non-African-American community-dwelling older adults in controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
120
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(142 citation statements)
references
References 21 publications
(26 reference statements)
19
120
3
Order By: Relevance
“…African Americans had similar rates of depressive symptoms compared with whites, a finding that is consistent with other studies in the general population (13,23) and among people with diabetes (15,22). In a recent study among men with type 2 diabetes by Fisher et al (24), white and AfricanAmerican men had lower depressive symptoms than Hispanic-and ChineseAmerican men, but these differences were not statistically significant after adjusting for income and education.…”
Section: Discussionsupporting
confidence: 82%
“…African Americans had similar rates of depressive symptoms compared with whites, a finding that is consistent with other studies in the general population (13,23) and among people with diabetes (15,22). In a recent study among men with type 2 diabetes by Fisher et al (24), white and AfricanAmerican men had lower depressive symptoms than Hispanic-and ChineseAmerican men, but these differences were not statistically significant after adjusting for income and education.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, the association between female sex and PTSD has also been reported in a community sample [24]. African-American race was reported to be a risk factor for psychological distress related to cancer [21], chronic pain-related depression [20]and psychosis associated with PTSD [25], but mixed results were reported for depressive symptoms [26, 27]. However, due to the scarcity of evidence on the risk of the wide range of mental disorders by age, sex, and race/ethnicity, the question whether there are sex and racial/ethnic differences regarding the type and frequency of different mental disorders in community-dwelling cancer patients is largely ignored.…”
Section: Introductionmentioning
confidence: 88%
“…Although at least that 10% of adults in the United States meet DSM-IV criteria for major depression, this prevalence differs by race, gender, and age [4]. Although several studies have shown that MDD may have a lower prevalence among African Americans than Whites in the U.S. [5][6][7], other reports suggest that African Americans may experience higher severity of depressive symptoms than Whites [8]. Depression tends to be more chronic, severe, and disabling for African Americans [7,9].…”
Section: Depression and African Americansmentioning
confidence: 99%